UPAYA PEMELIHARAAN KESEHATAN PADA KORBAN BANJIR ROB - Nurul Khasanah; Artika Nurrahima (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
The North Semarang region has a very high frequency of tidal flooding. Therefore, it is very necessary to maintain health for victims of tidal flooding. Health care efforts are useful to anticipate, and prevent health problems that may occur afterward. Previous research was still limited to address medication problems so that this study performed preventive health care efforts. This study aims to explore the experience of tidal flooding victims related to their health care efforts in Terboyo Wetan Village, District of Semarang Genuk, in 2019. This qualitative research was combined with a qualitative descriptive approach. Semi-structured in-depth interviews were further employed. The samples of this research were five participants selected using purposive sampling technique. Then, the data were analyzed by a method, namely thematic analysis. This study identified three themes, which include: (1) The impact of tidal flooding experienced by the community, (2) Health care efforts for victims of tidal flooding, and (3) Health services during tidal flooding. Health care efforts that have not been maximized are efforts to prevent the emergence of health problems due to tidal flooding as indicated by the limited use of boots, and inappropriate manners in maintaining sanitation, and health. Those can be observed from only a few participants who cleaned the house, and the environment properly. The efforts done by the participants are still considered less appropriate in preventing the spread of disease. In other words, health care efforts at the prevention stage have not been yet effective although the treatment stage has been already optimal. At last, to conduct further research regarding the factors that influence health care efforts for victims of tidal floods is also expected in the future.